Photoluminescence from Two-Phase Nanocomposites Embedded in Polymers - Mithun Bhowmick; James Christensen; Richard Adjorlolo; Bruno Ullrich (Micromachines, 2024)
A set of polymer-embedded, two-colored nanocomposites were prepared where the co-existing emission peaks (~578 nm and ~650 nm) had different ratios at their emission thresholds. The nanocomposite samples were simultaneously excited by a 405 nm laser, and the growth of photoluminescence intensities was studied as a function of excitation intensity. The two peaks showed different growth evolution mechanisms. The factors impacting this difference could be (1) energy transfer between the two sized nanoparticles; (2) relaxation mechanism of smaller nanoparticles; and (3) material properties of the polymer.